A New Strategy for Rejuvenating Primary Healthcare: The Government-Society Partnership Model - Siddarth S. Kasi (SAGE Publishing, 2023)
Primary healthcare systems worldwide are under stress as increased demands during pandemic surges have exposed deficiencies in the system. Primary healthcare centers have significant responsibilities but are often underfunded and understaffed. Recent events, including the COVID-19 pandemic, have highlighted the importance of a strong primary health center network to promote community health and save lives. Most governments have multiple competing financial needs for scarce resources, ultimately limiting the advancement of government primary healthcare systems. Hence, various models involving collaboration and outsourcing have been evaluated and employed to improve primary health services. We propose and describe a sustainable and scalable government-society partnership model to bridge the gulf and rejuvenate primary healthcare with a focus on the Indian healthcare system. The involvement of key stakeholders, including society, non-government organizations, and corporate sponsors, is essential to rebuild the network.